Personal Responsibility for Health: Exploring Together with Lay Persons. (25th July 2022) - Asada, Yukiko; Brown, Marion; McNally, Mary; Murphy, Andrea; Urquhart, Robin; Warner, Grace
Abstract: Emerging parallel to long-standing, academic and policy inquiries on personal responsibility for health is the empirical assessment of lay persons' views. Yet, previous studies rarely explored personal responsibility for health among lay persons as dynamic societal values. We sought to explore lay persons' views on personal responsibility for health using the Fairness Dialogues, a method for lay persons to deliberate equity issues in health and health care through a small group dialogue using a hypothetical scenario. We conducted two 2-h Fairness Dialogues sessions ( n  = 15 in total) in Nova Scotia, Canada. We analyzed data using thematic analysis. Our analysis showed that personal choice played an important role in participants' thinking about health. Underlying the concept of personal choice was considerations of freedom and societal debt. In participants' minds, personal and social responsibilities co-existed and they were unwilling to determine health care priority based on personal responsibility. The Fairness Dialogues is a promising deliberative method to explore lay persons' views as dynamic values to be developed through group dialogues as opposed to static, already-formed values waiting to be elicited.